Incidence of severe hypoglycemia and its association with serum adiponectin in Japanese patients with type 1 and insulin‐treated type 2 diabetes: The Fukuoka Diabetes Registry. Issue 5 (26th April 2020) - Iwase, Masanori; Komorita, Yuji; Fujii, Hiroki; Ohkuma, Toshiaki; Ide, Hitoshi; Yoshinari, Masahito; Oku, Yutaro; Higashi, Taiki; Nakamura, Udai; Kitazono, Takanari
Abstract: Aims/Introduction: The incidence of severe hypoglycemia and its risk factors including an insulin‐sensitizing adipokine, adiponectin, were prospectively investigated in Japanese patients with type 1 or insulin‐treated type 2 diabetes. Materials and Methods: A total of 207 participants with type 1 diabetes (mean age 55 years) and 1, 396 with insulin‐treated type 2 diabetes (mean age 65 years) from the local diabetes registry were followed for 5 years (follow‐up rate 99%). Severe hypoglycemia was defined as events requiring the assistance of others for recovery from hypoglycemia. Results: The incidence of severe hypoglycemia was 9.2 per 100 person‐years in those with type 1 diabetes, and 2.3 per 100 person‐years in those with insulin‐treated type 2 diabetes, respectively. For type 1 diabetes, the risk was significant in those with a history of severe hypoglycemia within the previous year, slow eating and higher serum adiponectin (the highest vs the lowest in quartile hazard ratio 2.36, 95% confidence interval 1.22–4.69). For insulin‐treated type 2 diabetes, the risk included age ≥65 years, history of severe hypoglycemia within the previous year, alcohol consumption ≥60 g/day, larger insulin dose and higher serum adiponectin (the highest vs the lowest in quartile, hazard ratio 2.95, 95% confidence interval 1.22–4.69). For all participants, the incidence of severe hypoglycemia increased along with serum adiponectin (age‐ and sex‐adjusted hazard ratio 1.65 per 1 standard deviation increase of log serum adiponectin, 95% confidence interval 1.45–1.87). Conclusions: The incidence of severe hypoglycemia was prospectively determined, and the association between severe hypoglycemia and higher serum adiponectin was observed in Japanese patients with type 1 and insulin‐treated type 2 diabetes. Abstract : The incidence of severe hypoglycemia was prospectively determined in Japanese patients with type 1 and insulin‐treated type 2 diabetes. The development of severe hypoglycemia was associated with higher serum adiponectin level.